Native Experience with a Tone Language Enhances Pitch Discrimination and the Timing of Neural Responses to Pitch Change - Giuliano, Ryan J.; Pfordresher, Peter Q.; Stanley, Emily M.; Narayana, Shalini; Wicha, Nicole Y. Y. (Frontiers in Psychology, 2011)
Native tone language experience has been linked with alterations in the production and perception of pitch in language, as well as with the brain response to linguistic and non-linguistic tones. Here we use two experiments to address whether these changes apply to the discrimination of simple pitch changes and pitch intervals. ERPs were recorded from native Mandarin speakers and a control group during a same/different task with pairs of pure tones differing only in pitch height, and with pure tone pairs differing only in interval distance. Behaviorally, Mandarin speakers were more accurate than controls at detecting both pitch and interval changes, showing a sensitivity to small pitch changes and interval distances that was absent in the control group. Converging evidence from ERPs obtained during the same tasks revealed an earlier response to change relative to no-change trials in Mandarin speakers, as well as earlier differentiation of trials by change direction relative to controls. These findings illustrate the cross-domain influence of language experience on the perception of pitch, suggesting that the native use of tonal pitch contours in language leads to a general enhancement in the acuity of pitch representations.